2022
DOI: 10.1101/2022.07.26.501446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinctive chaperonopathy in skeletal muscle associated with the dominant variant inDNAJB4

Abstract: DnaJ homolog, subfamily B, member 4, a member of the heat shock protein 40 chaperones encoded by DNAJB4, is highly expressed in myofibers. We identified a heterozygous c.270 T>A (p.F90L) variant in DNAJB4 in a family with a dominantly inherited distal myopathy, in which affected members have specific features on muscle pathology represented by the presence of cytoplasmic inclusions and the accumulation of desmin, p62, HSP70 and DNAJB4 predominantly in type 1 fibers. Both Dnajb4-F90L knock-in and knockout mi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…DNAJB4 is implicated in skeletal muscle proteostasis [ 74 ] and Alzheimer’s disease [ 75 ]. In addition, accumulating studies have suggested that DNAJB4 is involved in various cancers as a tumor suppressor that could inhibit cancer cell proliferation, invasion, and metastasis.…”
Section: Multi-faceted Roles Of Dnajb Protein In Cancer Metastasismentioning
confidence: 99%
“…DNAJB4 is implicated in skeletal muscle proteostasis [ 74 ] and Alzheimer’s disease [ 75 ]. In addition, accumulating studies have suggested that DNAJB4 is involved in various cancers as a tumor suppressor that could inhibit cancer cell proliferation, invasion, and metastasis.…”
Section: Multi-faceted Roles Of Dnajb Protein In Cancer Metastasismentioning
confidence: 99%